Spain and Russia in the Life of Agustin de Betancourt - Olga V. Volosyuk (RUDN Journal of Russian History)
The article examines the main stages of the life and activity of Spanish engineer Agustin de Betancourt who exerted a significant influence on the development of engineering in Russia at the beginning of the XIX century and made a significant contribution to the formation of the country's cultural heritage. Particular attention is paid to the poorly studied aspects of his biography: the reasons for moving from Spain to Russia and the role played by Russian ambassador to Madrid Ivan Muravyov-Apostol in the move, as well as specification of some previously unknown details of his stay in the Russian Empire. Based on the documents from Russian archives (the Archive of Foreign Policy of the Russian Federation, the State Archive of the Russian Federation) and Spanish archives (the National Historical Archive, the General Archive of the Indies, the Historical Archive of the Nobility), on the documents from Orotava Foundation in the Canary Islands, as well as on memoirs, the study traces the peculiarities of Agustin de Betancourt’s relationship with Emperor Alexander I, whose favorable disposition initially granted Betancourt carte-blanche in his work. The author comes to the conclusion that the disgrace of Agustin de Betancourt led to the “oblivion” of his contribution to the architectural and engineering image of St. Petersburg for almost a century. It is proved that apart from the monarch’s disgrace, a certain role was played by architect Auguste de Montferrand for this disgrace, who had grabbed the credit for his joint work with the Spanish engineer for himself.